The impact of information sharing on supply chain learning and flexibility performance. Issue 5 (4th March 2021) - Huo, Baofeng; Haq, Muhammad Zia Ul; Gu, Minhao
Abstract : Despite the importance of supply chain learning for competitiveness, little is known about how to enable such learning. This study empirically investigates the impact of information sharing on different types of supply chain learning (internal, supplier, and customer learning) and their influences on flexibility performance. Grounded in absorptive capacity theory, we use structural equation modelling to test the conceptual model based on data collected from 213 manufacturing firms in China. We find that supplier and customer learning improve internal learning. Further, our findings indicate that information sharing improves all three dimensions of supply chain learning. We also find that internal and customer learning have direct influences on flexibility performance, whereas internal learning mediates the relationship between supplier learning and flexibility performance. Moreover, information sharing moderates the relationship between supplier learning and flexibility performance. Our findings contribute to the literature and offer a new framework to understand the relationship between information sharing, supply chain learning and flexibility performance. The findings also furnish managers to seek competitive advantage through information sharing and supply chain learning.